A spatio-correlation-based reconstruction of 40-year nutrient and diatom-dinoflagellate community dynamics in Laizhou Bay, China - Guangshen Tan; Kan Chen; Ruobing Na; Haoyu Zhang; Xianli Song; Keqiang Li (Water Research, 2027)

Backwashing-induced nitrous oxide emissions in denitrifying biofilters: Dissolved N2O accumulation, physical stripping, and enzymatic imbalance - Jiabo Chen; Huiling Chen; Dingyu Hu; Ziding Ao; Ruobing Li; Baohua Tang; Hongchen Wang; Lu Qi; Guohua Liu (Bioresource Technology, 2026)

Decoupling dissolution and reaction for low-impurity synthesis of TDA through solvent-controlled activation and microreactor intensification - Ruobing Xin; Yongqi Pan; Libin Zhang; Yunlong Zhao; Yujun Wang; Qiang Chen; Guangsheng Luo (Chemical Engineering Journal, 2026)

Water-triggered microphase reconstruction enables anti-swelling ion transport in amphiphilic ionogels for adaptive multimodal sensing - Yu Zhang; Ruobing Tian; Xueming Tang; Zengguang Ji; Jiahao Liu; Xinli Wang; Guojun Deng; Bin Miao; Yuanna Sun; Hongyang Chen; Yongxing Wang (Chemical Engineering Journal, 2026)

The ecological footprint of green solvents: A multi-level assessment of ionic liquids toxicity in aquatic environments - Guo Chen; Xiaoni Chen; Ruobing Liu; Huan Wang; Ying Xu; Jiake Xu; Cheng Zhang; Jun Wang; Lusheng Zhu (Journal of Hazardous Materials, 2026)

Nanocarbon catalyzed ethylbenzene oxidative dehydrogenation: Intrinsic activity enhancement via electronic structure modulation with transition metals - Xueya Dai; Miao Guo; Kunru Fan; Ruobing Chen; Mu Niu; Zhifeng Gao; Wei Qi (Chemical Engineering Journal, 2026)

Crafting cellulose hollow microspheres with cellulose nanosheets - Wenxuan Lei; Heng Huang; Ruobing Liang; Guoping Li; Pan Chen; Jiechun Xiang; Ang Lu (Carbohydrate Polymers, 2026)

Global spread and evolution of KPC-2 and NDM-1-producing Gram-negative bacteria - Meng Cai; Kaiwen Song; Chaoqun Yao; Shuyi Wang; Ruobing Wang; Qi Wang; Hongbin Chen; Hui Wang (Science China Life Sciences, 2026)
The co-occurrence of KPC and NDM carbapenemases in Gram-negative bacteria presents a serious and expanding global health threat. This study characterized 338 KPC-2/NDM-1 dual-positive isolates from 23 countries, including 41 clinical strains sequenced through hybrid second- and third-generation platforms from China’s national surveillance network. These isolates spanned six genera, 58 species, and 138 sequence types, reflecting substantial taxonomic and geographic diversity. Molecular analysis identified IncFII(p14) plasmids as the principal vectors for cross-genus dissemination of KPC-2, while IncX3, IncN, and IncFIB(pB171)/IncFII(Yp) plasmids were dominant carriers of NDM-1 among the studied strains. Codon usage analysis indicated stronger bias in KPC-2 plasmids (effective codon number: 39.17, optimal codons: 17) compared to NDM-1 plasmids (effective codon number: 41.25, optimal codons: 12), indicating differential evolutionary pressures. Dual-positive strains exhibited significantly higher virulence scores and broader resistance profiles than reference strains ( P <0.001). Notably, only 14.6% of isolates harbored Type I–E CRISPR-Cas systems, all of which encoded the anti-CRISPR protein AcrIE10. Furthermore, Type II methyltransferase numbers were significantly enriched in dual-positive strains ( P <0.005), suggesting a potential role in modulating host defense evasion. We propose that in Klebsiella spp., KPC-2 plasmids are typically acquired prior to NDM-1 plasmids and can form hybrid plasmids. In non- Klebsiella genera, dual resistance is primarily driven by independent acquisition of high-risk plasmids such as IncFII(p14) and IncX3, without a fixed temporal order. These findings highlight the convergence of global plasmid-mediated resistance, host-pathogen immune interplay, and pan-resistance evolution. Targeting high-risk plasmid lineages and host defense-modulating elements may be key to forecasting resistance emergence and guiding early interventions against dual-carbapenemase-producing pathogens.

HFPO-TA induces cardiac developmental damage in zebrafish by disrupting mitochondrial dynamics through FABP3 - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao (Environmental Research, 2026)

A Segatella Copri-centered Gut Microbiota-mediated Metabolic Dysregulation Associated with Transition from Asymptomatic to Symptomatic Intracranial Atherosclerosis - Manqi Zheng; Xiao Yang; Ruobing Tian; Xue Xia; Qin Xu; Ying Hui; Shuohua Chen; Yan Liu; Anxin Wang (Translational Stroke Research, 2026)

The novel PFOS substitute OBS induces visual developmental toxicity in zebrafish embryos via ferroptosis - Xing Liu; Xinyi Wu; Mingzhu Xia; Yi Fan; Yichun Zhao; Junjie Han; Ruobing Chen; Yuting Peng; Man Qu (Toxicology Letters, 2026)

Nomilin ameliorates perfluorooctanoic acid (PFOA)-induced impairment of zebrafish (Danio rerio) ocular development and visual function through PIK3CA activation - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao; Man Qu (Toxicology and Applied Pharmacology, 2026)

Cu-doped OMS-2 catalysts for photothermal synergistic VOCs segradation: Efficiency enhancement under UV-Vis irradiation in flow conditions - Yunchao Liu; Xinyu Qi; Xiang Bai; Yuanli Lu; Jing Sun; Chen Wang; Tingting Shen; Hao Liu; Yanyan Liu; Jiaqi Zhao; Tianyu Ji; Ruobing Liu; et al. (Journal of Environmental Sciences, 2026)

Nomilin mitigates OBS-induced developmental cardiotoxicity via the Nrf2 pathway - Xing Liu; Yi Fan; Ruobing Chen; Yuting Peng; Xinyi Wu; Mingzhu Xia; Yichun Zhao; Junjie Han; Man Qu (Aquatic Toxicology, 2026)

Cross-patient seizure prediction via continuous domain adaptation and similar sample replay - Ziye Zhang; Aiping Liu; Yikai Gao; Ruobing Qian; Xun Chen (Cognitive Neurodynamics, 2025)

Galvanic effects between mackinawite and pyrogenic carbon: Enhancing radical-mediated ciprofloxacin transformation - Danning Lu; Longgang Chu; Haoran Yu; Zhaoyue Sun; Xiru Chen; Ruobing Wang; Xing Liu; Zhanghao Chen; Juan Gao; Cheng Gu (Journal of Hazardous Materials, 2025)

Multi-omics insights into 6PPD- and 6PPDQ-induced gut-liver axis disruption and non-alcoholic fatty liver disease progression in zebrafish (Danio rerio) - Yu Feng; Hongyi Xian; Ruobing Bai; Zhiming Li; Hao Li; Long Zhang; Xiyun Huang; Yuji Huang; Boxuan Liang; Yanhong Deng; Xiaohong Yang; Xiaoqing Chen; et al. (Journal of Hazardous Materials, 2025)

Lactic acid bacteria fermentation: A novel and promising pathway to lower the uric acid production of seaweed food (Porphyra haitanensis) - Yuting Dong; Xinyao Chao; Ruobing Li; Jinli Chen; Jinzhong Cai; Yang Yang; Yuanqing Lin (International Journal of Food Microbiology, 2025)

The preservation effect of curcumin-containing emulsion on the freshness of crisp grass carp during refrigerated storage - Chengang Zhao; Chao Ai; Ruobing Wang; Xuanlin Luo; Hui Teng; Lei Chen (Food Bioscience, 2025)

The role of developmental and climate factors in driving autumn phenology across the Northern Hemisphere - Shuping Ji; Shilong Ren; Xiaoyang Zhang; Ruobing Liu; Zhenyu Gao; Changchao Li; Lei Fang; Jinyue Chen; Xinfeng Wang; Guoqiang Wang; Qingzhu Zhang; Qiao Wang (Agricultural and Forest Meteorology, 2025)

The post-effects of landscape practices on spontaneous plants in urban parks - Chundi Chen; Ruobing Wang; Mingkun Chen; Juanjuan Zhao; He Li; Maria Ignatieva; Weiqi Zhou (Urban Forestry & Urban Greening, 2025)

Harnessing multi-target nanosweepers inhibiting β-amyloid aggregation, scavenging reactive oxygen species and overcoming the blood brain barrier for rescuing Alzheimer’s disease - Yixuan Wang; Chaoren Yan; Yuming Qi; Ruobing Zhao; Yan Wan; Zhaoyuan Lyu; Yansong Li; Zhijuan Wang; Changqing Li; Yuehe Lin; Qian Chen; Shichao Ding; et al. (Chemical Engineering Journal, 2025)

Privacy-preserving multi-source semi-supervised domain adaptation for seizure prediction - Deng Liang; Aiping Liu; Le Wu; Chang Li; Ruobing Qian; Xun Chen (Cognitive Neurodynamics, 2024)

Gender-specific effects of polystyrene nanoplastic exposure on triclosan-induced reproductive toxicity in zebrafish (Danio rerio) - Zhiming Li; Hongyi Xian; Rongyi Ye; Yizhou Zhong; Boxuan Liang; Yuji Huang; Mingzhu Dai; Jie Guo; Shuqin Tang; Xiaohu Ren; Ruobing Bai; Yu Feng; et al. (Science of The Total Environment, 2024)

From cradle to grave: Deciphering sex-specific disruptions of the nervous and reproductive systems through interactions of 4-methylbenzylidene camphor and nanoplastics in adult zebrafish - Hongyi Xian; Zhiming Li; Ruobing Bai; Rongyi Ye; Yu Feng; Yizhou Zhong; Boxuan Liang; Yuji Huang; Jie Guo; Binjie Wang; Mingzhu Dai; Shuqin Tang; et al. (Journal of Hazardous Materials, 2024)

Preparation of novel gallic acid-based dummy-template molecularly imprinted polymer adsorbents for rapid adsorption of dibutyl phthalate from water - Shunying Li; Yuanhao Zhou; Qiangqiang Xu; Haoxiang Chen; Shengpeng Shi; Ruobing Jia; Yingying Zhang; Hong Ye (Environmental Pollution, 2024)

LDHA and LDHB overexpression promoted the Warburg effect in malignantly transformed GES-1 cells induced by N-nitroso compounds - Xing Liu; Xihuan Zou; Yueyue Zhou; Ruobing Chen; Yuting Peng; Man Qu (Food and Chemical Toxicology, 2023)

4-Methylbenzylidene camphor triggers estrogenic effects via the brain-liver-gonad axis in zebrafish larvae - Hongyi Xian; Zhiming Li; Rongyi Ye; Mingzhu Dai; Yu Feng; Ruobing Bai; Jie Guo; Xiliang Yan; Xingfen Yang; Da Chen; Zhenlie Huang (Environmental Pollution, 2023)

Construction of BiOCl/Ti-MOFs type-II heterojunction photocatalyst for enhanced photocatalytic performance for multiple antibiotics removal - Chengwei Wang; Zhuhuan Chen; Ruobing Yu (Environmental Science and Pollution Research, 2023)

Damage-control design and hybrid tests of a full-scale two-story buckling-restrained braced steel moment frame with sliding gusset connections - Junxian Zhao; Lijian Yan; Chen Wang; Yun Zhou; Ruobing Chen; Tak-Ming Chan (Engineering Structures, 2023)

Complete genome sequence of a novel rhabdo-like virus from the Chinese black cutworm Agrotis ipsilon (Lepidoptera: Noctuidae) - Su Chen; Haichao Li; Guohui Yuan; Ruobing Guan; Tong Li (Archives of Virology, 2020)

A pair of chiral flavonolignans as novel anti‐cyanobacterial allelochemicals derived from barley straw ( H ordeum vulgare ): characterization and comparison of their anti‐cyanobacterial activities - Xi Xiao; Haomin Huang; Zhiwei Ge; Trine B. Rounge; Jiyan Shi; Xinhua Xu; Ruobing Li; Yingxu Chen (Environmental Microbiology, 2014)
Summary The inhibitory effect of barley straw ( H ordeum vulgare ) on cyanobacteria has been observed in many field and laboratory studies for over 30 years, although the compounds responsible for this anti‐cyanobacterial effect have remained unknown. In this study, a pair of chiral flavonolignans were isolated from barley straw extract using a bioassay‐guided isolation procedure against M icrocystis sp. The structures of the allelopathic compounds were elucidated by NMR (nuclear magnetic resonance) and HPLC‐MS (high performance liquid chromatography‐mass spectrometry), and turned out to be salcolin A and B . The enantiomers differ in their anti‐cyanobacterial abilities. Both enantiomers exhibited inhibitory effects on M icrocystis sp ., and the EC 50 (concentration for 50% of maximal effect) of salcolin A and B were 6.02 × 10 −5 and 9.60 × 10 −5 mol l −1 , respectively. Furthermore, the modes of actions of the enantiomers were investigated and compared at a single cell level by flow cytometry. Salcolin A was found to induce an increase on cyanobacterial intracellular ROS (reactive oxygen species) levels and to inhibit esterase activity, whereas salcolin B caused leakages of cyanobacterial cytoplasms. Thus, salcolin A was more ‘algistatic’, and salcolin B was more ‘algicidal’. This study suggests that salcolin is the key allelochemical in barley straw's inhibitory effect on cyanobacteria and could be used as an agent in the future control of cyanobacterial harmful algae blooms.